1993
DOI: 10.1177/019262339302100606
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxic Lesions Induced by Quinolone Antibacterial Agents in Auricular Skin and Retina of Albino Mice

Abstract: The phototoxic effects of quinolone antimicrobial agents on mouse auricular skin and retina were examined histologically. Sparfloxacin at 50 or 100 mg/kg, which alone causes no histologic change, was orally administered to albino Balb/c mice, which were irradiated with ultraviolet A for 4 hr immediately after administration. In the auricle, degeneration of basal epidermal cells was sporadically observed at 2 hr (during the irradiation). Foci of slight edema with degenerated fibroblasts were seen in the dermis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…In contrast, treatment with LVFX up to 100 /ZM and UVA had no effect on PG concentration in the 3T3 cell culture medium. This lesser effect of LVFX in contrast to that of SPFX appears to be consistent with our previous in vivo study, in which oral administration of 50 mg/kg SPFX or 800 mg/kg LVFX followed by UVA irradiation induced auricular inflammation, while that of 400 mg/kg LVFX with UVA did not (Shimoda et al, 1993). Quinolones substituted with a fluorine at the 8 position of the quinolone ring have been reported to possess stronger phototoxic potential than quinolones with other substituents at this position (Domagala, 1994).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, treatment with LVFX up to 100 /ZM and UVA had no effect on PG concentration in the 3T3 cell culture medium. This lesser effect of LVFX in contrast to that of SPFX appears to be consistent with our previous in vivo study, in which oral administration of 50 mg/kg SPFX or 800 mg/kg LVFX followed by UVA irradiation induced auricular inflammation, while that of 400 mg/kg LVFX with UVA did not (Shimoda et al, 1993). Quinolones substituted with a fluorine at the 8 position of the quinolone ring have been reported to possess stronger phototoxic potential than quinolones with other substituents at this position (Domagala, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of our having previously demonstrated that auricular skin inflammation was induced by quinolone phototoxicity in Balb/c mice (Shimoda et al, 1993), Balb/c 3T3 mouse fibroblast cells obtained from American Type Culture Collection and maintained in our laboratory were used in the present study. The cells were seeded in 12-well culture plates coated with collagen type I (Iwaki Glass, Japan) at a uniform density of 5 X 10 4 cells/ml in RPMI medium 1640 with phenol red, supplemented with 10% FBS, penicillin (100 /zg/ml), and streptomycin (100 units/ml), followed by incubation for 72 hr at 37°C in a humidified 5% CO 2 incubator to approximately 100% monolayer confluence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their recent article, Shimoda et al (5) reported the occurrence of retinal atrophy in albino mice induced by quinolone. They stated, &dquo;Few reports have dealt with morphologic changes induced by drug phototoxicity; in particular, we are aware of no studies concerning retinal changes&dquo; (p. 555).…”
mentioning
confidence: 99%